2012
DOI: 10.1037/a0028083
|View full text |Cite
|
Sign up to set email alerts
|

Testing the integration of ICF and behavioral models of disability in orthopedic patients: Replication and extension.

Abstract: Objective: Disability from chronic illness is a major problem for society, yet the study of its determinants lacks an overall theoretical paradigm. Johnston (1996) has proposed conceptualizing disability as behavior and integrating biomedical and behavioral predictors. Dixon, Johnston, Rowley, and Pollard (2008) tested a model including constructs from the International Classification of Functioning, Disability and Health (ICF) and the theory of planned behavior (TPB) using structural equation modeling; it fit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
14
0

Year Published

2013
2013
2016
2016

Publication Types

Select...
6
2

Relationship

4
4

Authors

Journals

citations
Cited by 18 publications
(17 citation statements)
references
References 61 publications
3
14
0
Order By: Relevance
“…Pollard et al (2009) identified pure measures of ICF constructs, uncontaminated by the other constructs in the model, making it possible to test theoretical models of the relationships between constructs in the ICF and to test theoretical models that integrate the ICF with psychological models (Dixon, Johnston, Elliott, & Hannaford, 2011;Dixon, Johnston, Rowley, & Pollard, 2008;Quinn et al, 2012). Pollard et al (2009) identified pure measures of ICF constructs, uncontaminated by the other constructs in the model, making it possible to test theoretical models of the relationships between constructs in the ICF and to test theoretical models that integrate the ICF with psychological models (Dixon, Johnston, Elliott, & Hannaford, 2011;Dixon, Johnston, Rowley, & Pollard, 2008;Quinn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Pollard et al (2009) identified pure measures of ICF constructs, uncontaminated by the other constructs in the model, making it possible to test theoretical models of the relationships between constructs in the ICF and to test theoretical models that integrate the ICF with psychological models (Dixon, Johnston, Elliott, & Hannaford, 2011;Dixon, Johnston, Rowley, & Pollard, 2008;Quinn et al, 2012). Pollard et al (2009) identified pure measures of ICF constructs, uncontaminated by the other constructs in the model, making it possible to test theoretical models of the relationships between constructs in the ICF and to test theoretical models that integrate the ICF with psychological models (Dixon, Johnston, Elliott, & Hannaford, 2011;Dixon, Johnston, Rowley, & Pollard, 2008;Quinn et al, 2012).…”
Section: Discussionmentioning
confidence: 99%
“…Impairment (joint pain) and self-efficacy were predictive whereas OE did not predict walking limitations either in the SCT or the integrated model (Dixon, 2006). In the replication study, SCT accounted for 60% and the integrated model 64 % of variance in AL (Quinn et al, 2012). Following joint replacement surgery, the SCT explained 79% variance and the integrated model 82% variance in AL.…”
Section: Tests Of the Integrated Icf/sct Modelmentioning
confidence: 93%
“…In each of these studies, measures of A and AL were selected on the basis of empirical work using Discriminant Content Validity methods ( Pollard et al, 2006;Pollard et al, 2009) to ensure satisfactory operationalization of these (Quinn , Johnston, Dixon, Johnston, Pollard, 2012). Table 1 about here While these findings offer considerable support for an integrated model, they are confined to one population, health condition and level of impairment and disability.…”
Section: Tests Of the Integrated Icf/tpb Modelmentioning
confidence: 99%
See 1 more Smart Citation
“…To date, the integrated model has been tested using group-based designs identifying differences in activity limitations and walking between individuals with disabling chronic conditions including osteoarthritis (Dixon, Johnston, Rowley, & Pollard, 2008;Quinn et al, 2012), chronic pain (Dixon, Johnston, Elliott, & Hannaford, 2012), and chronic idiopathic axonal polyneuropathy (Schroder et al, 2007). However, the majority of psychological theories posit within-individual processes, and therefore, the importance of testing whether a model or theory can account for differences in behaviour within an individual is paramount (Curran & Bauer, 2011;.…”
Section: Statement Of Contributionmentioning
confidence: 99%